As cren??as religiosas e espirituais do idoso no enfrentamento dos desafios advindos das feridas cr??nicas - Coulibaly, Abdoulaye (2015)
Old age is a challenge for everyone and for the sciences, which enabled an increase in life expectancy worldwide. Aging causes changes in various aspects that determine greater fragility front of pathological processes, making individuals more susceptible to disease. Caregivers of elderly, formal or informal, looking aside decisions and procedures with the elderly and when they are suffering from chronic wounds, then face a bigger challenge. The main factors that have been identified in this research shows that there is influence in addressing chronic wounds by caregivers, which were grouped into five areas (or environments): physiological, psychosocial, economic, political and spiritual. Chronic wounds cause changes in the life of the person from the disease undergoes changes in its pattern and lifestyle and begins to live according to your problem, giving up the things they like and the activities they performed. Besides involving issues with the appearance and limitations, the disease also undermines the "psyche" due to changes in self-image, affective and emotional life. This study aims to investigate how religion and spirituality can help in coping with chronic wounds. It is a study of observational descriptive, cross-sectional design and qualitative and quantitative approach. The results showed that patients with chronic wounds elderly addition to turn to medical help, make use of their faith in God for healing and improving their quality of life. The data indicate the relevance of the study on the elderly possessors of chronic wounds, the humanized medical care and the importance given by them about the religious aspects and faith in the healing process.